Tocopherol induced angiogenesis in placental vascular network in late pregnant ewes - Sponenberg Philip D; Pelzer Kevin D; Rodriguez Jacobo S; Kasimanickam Vanmathy R; Kasimanickam Ramanathan K; Thatcher Craig D (BMC, 2010)
Abstract Background Tocopherols have biphasic, proangiogenic and antiangiogenic therapeutic effects. The objective of this clinical trial was to clarify tocopherol's placental angiogenic potential in late pregnant ewes following oral supplementation. Methods Eighteen pregnant ewes during late gestation were selected for this study. Ewes were given oral supplementation of 500 mg of alpha-tocopherol (aT; N = 6) or 1000 mg of gamma-tocopherol (gT; N = 7) or placebo (CON; N = 5) once daily from 107 to 137 days post breeding. Serum was obtained at weekly intervals and tissue samples were obtained at the end of supplementation to: 1) evaluate tocopherol concentrations in serum, uterus and placentome; 2) evaluate relative mRNA expressions of Vascular Endothelial Growth Factor (VEGF), Placental Growth Factor (PlGF), endothelial Nitric Oxide Synthase (eNOS) and Hypoxia Inducible Factors (HIF) in uterus, caruncle and cotyledon; 3) analyze the morphometry of the placental vascular network. Results Supplementation of aT or gT resulted in increased concentrations in serum, placentome and uterus compared to control (P < 0.05). In aT group, mRNA expressions of PlGF, eNOS and HIF-1α in cotyledon were greater than the CON group. In gT group, mRNA expressions of VEGF, eNOS, HIF-1 alpha and HIF-2 alpha in caruncle and uterus, and HIF-1α in cotyledon, were greater than the CON group. Morphometry analysis revealed increased angiogenesis in the supplemented groups. Conclusion Daily oral supplementation of aT or gT increased angiogenesis in the placental vascular network in pregnant ewes during late gestation. Increase in placental angiogenesis may provide nutrients required for the development and growth of fetus during late pregnancy.